The Impact of Studying Prophetic Hadiths on the Educational Behavior of Ninth-Grade Female Students in the State of Kuwait - Al-Ajami, Nora Faleh (Journal of Educational and Psychological Sciences, 2025)
This study aims to analyse the impact of teaching Prophetic Hadiths on the educational behavior of ninth-grade female students in the State of Kuwait. It evaluates the extent to which the Hadiths included in Unit Three of the Islamic Education textbook influence several behavioral domains, including commitment to worship, good manners, cooperation, patience, and preparedness for the Hereafter. The study adopted a descriptive-analytical methodology and employed an exploratory approach using two questionnaires administered to a sample of 156 students and 6 teachers. Data were analyzed using SPSS software. The results of the Kaiser-Meyer-Olkin test (KMO = 0.79) and Bartlett’s Test of Sphericity (Sig. = 0.000) confirmed the suitability of the data for exploratory factor analysis, which revealed a primary factor representing general educational behavior. Simple linear regression analysis further indicated that teaching Prophetic Hadiths explains approximately 76% of the variance in students’ behavior (R² = 0.76), a strong indicator of instructional effectiveness. The results showed a significant positive impact in areas of ethics and religious practice, with some variation in dimensions such as patience and remembrance (dhikr). Teachers’ responses were consistent with those of the students, reflecting shared educational perceptions and supporting the effectiveness of teaching Hadiths within the school environment. The study recommends integrating Prophetic Hadiths into both classroom and extracurricular educational practices to reinforce moral values and promote positive behavior in the school setting.